Coffee Shops and Daily life - Zantides, Evripides (My University, 2019)
he consumption of coffee in Cyprus is a ‘social ritual’ which takes place as part of everyday life. In fact, it is a quotidian practice to the extent that it becomes a feature of the local national identity. Self-dialogues I-VI are six visual poems that are produced based on this practice, as well as on the interior set-ups, and placement of people in coffee shops. The verbal messages derive from personal thoughts and memories that, while they are triggered by the space, they are also inspired by the interior smell of coffee, the surrounding voices, colours, lighting and noises that co-exist. More like abstract poetic statements, they are dialogues with oneself and aim to question what dreams are, the value of time, death, loss, identity and absence.